1991
DOI: 10.1128/jb.173.24.7963-7969.1991
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PDC6, a third structural gene for pyruvate decarboxylase in Saccharomyces cerevisiae

Abstract: Pyruvate decarboxylase is the key enzyme in alcoholic fermentation in yeast. Two structural genes, PDC1 and PDCS have been characterized. Deletion of either of these genes has little or no effect on the specific pyruvate decarboxylase activity, but enzyme activity is undetectable in mutants lacking both PDC1 and PDCS (S. Hohmann and H. Cederberg, Eur. J. Biochem. 188:615-621, 1990). Here I describe PDC6, a gene structurally closely related to PDC1 and PDCS. The product ofPDC6 does not seem to be required for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(143 citation statements)
references
References 32 publications
7
134
2
Order By: Relevance
“…In this study PDC1 was shown to exhibit relatively high transcription at 60 h, while the PDC5 gene, which is believed to function in the absence of PDC1 (Seeboth et al, 1990), did not show a significant change in transcription. Despite being considered relatively unimportant for alcoholic fermentation (Hohmann, 1991), the PDC6 gene had the highest fold increase in transcription of all the PDC genes. This may relate to an increased expression of the gene in the presence of ethanol (Hohmann, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study PDC1 was shown to exhibit relatively high transcription at 60 h, while the PDC5 gene, which is believed to function in the absence of PDC1 (Seeboth et al, 1990), did not show a significant change in transcription. Despite being considered relatively unimportant for alcoholic fermentation (Hohmann, 1991), the PDC6 gene had the highest fold increase in transcription of all the PDC genes. This may relate to an increased expression of the gene in the presence of ethanol (Hohmann, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Despite being considered relatively unimportant for alcoholic fermentation (Hohmann, 1991), the PDC6 gene had the highest fold increase in transcription of all the PDC genes. This may relate to an increased expression of the gene in the presence of ethanol (Hohmann, 1991). This result again emphasizes the disparity between laboratory-scale and full-scale fermentations.…”
Section: Discussionmentioning
confidence: 99%
“…Auxotrophy for Ade and Trp was introduced into the MK4416 strain to give the MK5316 strain, which was used as the parental mannitol-assimilating strain. The three genes for Pdc in S. cerevisiae (PDC1, PDC5, and PDC6) 16 were deleted in the MK5316 strain to give the Pdc-negative and mannitol-assimilating MK5376 strain (Table 1), which was confirmed to have no Pdc activity (Supplementary Results).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the PDC1 gene encoding pyruvate decarboxylase involved in acetaldehyde biosynthesis, which is necessary for cytosolic acetyl-CoA biosynthesis, is also disrupted in our recombinant strain. However, since S. cerevisiae possesses 3 genes encoding pyruvate decarboxylase isozymes (PDC1, PDC5 and PDC6 ), [26][27][28] our recombinant strain can produce acetaldehyde by the Pdc5p and Pdc6p proteins. Therefore, the reason why our recombinant strain shows low cell growth, glucose consumption and target product production rates of our recombinant strain is caused by disruption of the major metabolic reactions involved in NADH oxidation (i.e., ethanol and glycerol biosynthesis pathways) rather than the insufficiency of nutrients.…”
Section: Recombinant Strain Incapable Of Ethanol and Glycerol Biosyntmentioning
confidence: 99%